Three-dimensional artificial liver platforms for drug screening and tissue engineering applications - Ferracci, Gaia (Nanyang Technological University, 2020)
Drug-induced liver disease represents one of the most common causes of drug failure at the clinical and post-marketing phases, indicating that pre-clinical animal studies are not always fully predictive of a drug hepatotoxic effect. Hence, artificial systems able to reproduce liver functionality over extended periods of time would hold great potential for the prediction of drugs toxicities and thus would represent a great tool during the drug screening process, to lessen drug attrition rates, minimize the risks for patients and reduce in vivo animal studies. Over the past years, numerous researchers demonstrated that recapitulation of the features of the liver native microenvironment is crucial for maintaining a differentiated hepatic phenotype over extended time in culture. Therefore, the overall goal of this dissertation was to develop three-dimensional (3D) liver cell constructs for drug screening, characterized by a 3D in vivo-like liver microarchitecture (i.e., honeycomb organization) and an in vivo-like liver surface composition (i.e., presence of ECM proteins), as these were hypothesized to be the main in vivo-like characteristics required to maintain a differentiated hepatic phenotype in vitro. 3D inverted colloidal crystal (ICC) hydrogels were chosen as the scaffolding structure, as their highly porous architecture, characterized by highly interconnected and uniform cavities arranged in a hexagonal fashion, highly resembles liver lobules organization, and as their simple fabrication process allows mass production. ICCs were fabricated utilizing both synthetic and natural materials. Poly (ethylene glycol) diacrylate (PEGDA) was chosen as synthetic polymer, due to the promising results obtained from previous experiments conducted in our group and PEGDA ICCs were functionalized with either collagen type I or fibronectin in order to provide hepatocytes with a more in vivo-like liver surface composition. Bovine serum albumin (BSA) was chosen due to the potential shown in various regenerative medicine applications and due to its binding abilities, as BSA has shown to bind serum adhesive proteins such as fibronectin and few types of cancer cells. BSA was functionalized with methacryloyl groups, thus to obtain a material that can be photocrosslinked within minutes in complex shapes and that, due to the reduced viscosity, can be easily infiltrated into the lattice template. In the first part of this dissertation, 3D PEGDA-based ICC hydrogels were utilized to establish a functional porcine hepatocyte culture for the prediction of a drug hepatotoxicity. The performances of non-adhesive bare PEGDA ICCs and biofunctionalized PEGDA ICCs were investigated relatively to hepatocytes morphology, viability, hepatic-specific functions, and gene expression over a period of 2 weeks in culture and after repeated exposure to diclofenac. Primary porcine hepatocytes were chosen for their large availability and biotransformation similarity to human hepatocytes. Hepatocytes cultured in the ICC 3D environment outperformed hepatocytes cultured in the two-dimensional (2D) monolayer culture, and their aggregation patterns and hepatic-specific functionality, which were correlated with the ECM proteins on the hydrogel surface, indicated that a 3D environment coupled with the presence of ECM proteins, especially fibronectin, better support hepatocyte viability and maintain in-vitro liver-specific phenotype, enabling the prediction of hepatotoxicity caused by the drug diclofenac. In the second part of this dissertation, the synthesis of BSA methacryloyl (BSA-MA) with different degrees of methacryloylation (DM) and the physio-biochemical properties of photocurable BSA-MA bulk hydrogels, with different DM and at different concentrations, were systematically investigated. In particular, the swelling behavior, mechanical properties, degradation rate and biocompatibility of photocured BSA-MA hydrogels were examined in terms of physical tunability. In the last part of this dissertation, photocurable BSA-MA ICCs were fabricated and their physio-biochemical features, such as morphology, swelling, mechanical properties and enzymatic degradation investigated, along with their ability to support liver cells viability and functionality. Huh-7.5 cells were utilized as, being highly permissive to the hepatitis C virus, they might be useful for the screening of drugs for liver disease caused by hepatitis viruses. BSA-MA ICC hydrogels exhibited overall structural integrity with a geometrically defined porous microarchitecture, a modulus in the range of the healthy liver and supported the attachment and growth of Huh-7.5 cells, which presented viability and functionality similar to hepatic spheroids cultured in non-adhesive PEGDA ICC hydrogels. On the whole, the work presented in this dissertation demonstrated the potential of ICC hydrogels in the design of in vitro liver platforms for applications such as drug screening and tissue engineering and paved the way to use photocurable albumin methacryloyl hydrogels in regenerative medicine applications.